Phenotyping Green and Roasted Beans of Nicaraguan Coffea Arabica Varieties Processed with Different Post-Harvest Practices - Gaia Meoni; Claudio Luchinat; Enrico Gotti; Alejandro Cadena; Leonardo Tenori (Applied Sciences, 2021)
Metabolomic tecniques have already been used to characterize two of the most common coffee species, C. arabica and C. canephora, but no studies have focused on the characterization of green and roasted coffee varieties of a certain species. We aim to provide, using NMR-based metabolomics, detailed and comprehensive information regarding the compositional differences of seven coffee varieties (C. arabica) of green and roasted coffee bean batches from Nicaragua. We also evaluated how different varieties react to the same post-harvest procedures such as fermentation time, type of drying and roasting. The characterization of the metabolomic profile of seven different Arabica varieties (Bourbon-typica), allowed us also to assess the possible use of an NMR spectra of bean aqueous extracts to recognize the farm of origin, even considering different farms from the same geographical area (Nueva Segovia). Here, we also evaluated the effect of post-harvest procedures such as fermentation time and type of drying on green and roasted coffee, suggesting that post-harvest procedures can be responsible for different flavours. This study provides proof of concept for the ability of NMR to phenotype coffee, helping to authenticate and optimise the best way of processing coffee.